Vitamin B12 status and optimal range for hemoglobin formation in elite athletes - Krzywanski, J.; Mikulski, T.; Pokrywka, A.; Mlynczak, M.; Krysztofiak, H.; Fraczek, B.; Ziemba, A. (Nutrients, 2020)
Background: Athletes and coaches believe in the ergogenic effect of vitamin B12 (which results from enhanced erythropoiesis) and they often insist on its unjustified supplementation. Therefore, our study aimed to assess the vitamin B12 status in Polish elite athletes and its influence on red blood cell parameters. Methods: In total, 1131 blood samples were collected during six years from 243 track and field athletes divided into strength and endurance groups, as well as according to the declared use of vitamin B12 injections. Results: An average vitamin B12 concentration in all subjects was 739 ± 13 pg/mL, with no cases of deficiency. A weak but significant relationship was found between vitamin B12 and hemoglobin concentrations. A significant increase in hemoglobin appeared from very low vitamin B12 concentration and up to approx. 400 pg/mL, while hemoglobin did not significantly change from 700 pg/mL and onwards. Vitamin B12 injections were used by 34% of athletes, significantly more often by endurance than by strength athletes. In athletes who declared no use of injections, a higher concentration of vitamin B12 was observed in the endurance group. Conclusion: The main finding of the present study is the determination of the range of vitamin B12 concentration which may favor better hemoglobin synthesis in athletes. They should regularly monitor vitamin B12 concentration and maintain the range of 400-700 pg/mL as it may improve red blood cell parameters. We might suggest application of a supplementation if necessary. Special attention is required in athletes with a vitamin B12 concentration below 400 pg/mL.